2022
DOI: 10.1177/21925682211069936
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential Bone Fusion in Adult Spinal Deformity via Combination of Oblique Lateral Interbody Fusion and Grade 2 Posterior Column Osteotomy

Abstract: Study Design Retrospective study Objectives The combination of oblique lateral interbody fusion (OLIF) with grade 2 posterior column osteotomy (PCO) is an effective treatment for adult spinal deformity. However, grade 2 PCO may lead to pseudoarthrosis because it involves complete removal of the bilateral posterior facet joints. The main study objective was to determine the achievement rate of anterior and posterolateral fusion resulting in circumferential fusion in patients who underwent combined OLIF and grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Therefore, in this study, we developed two types of FEA model. In posterior correction procedures for ASD, the cantilever technique is the most important technique for appropriate lumbar lordosis [12,13]. To mimic the cantilever technique in the posterior correction procedure for ASD, we developed a simpli ed FEA model by shortening the distance between the consecutive spinous processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, in this study, we developed two types of FEA model. In posterior correction procedures for ASD, the cantilever technique is the most important technique for appropriate lumbar lordosis [12,13]. To mimic the cantilever technique in the posterior correction procedure for ASD, we developed a simpli ed FEA model by shortening the distance between the consecutive spinous processes.…”
Section: Discussionmentioning
confidence: 99%
“…If LLIF secures anterior bone fusion, we can acquire a relatively large amount of lumbar lordosis by performing multilevel grade 2 PCO without the potential risk of pseudoarthrosis for ASD. We previously showed that LLIF and grade 2 PCO are a good combination to acquire su cient lumbar lordosis and solid bone fusion for ASD and other lumbar degenerative diseases [13]. We have been applying this combined OLIF grade 2 PCO procedure in the treatment of these diseases and observed a very high percentage of circumferential bone fusion after surgery [13].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Meanwhile, grade 2 posterior column osteotomy (PCO) is a very effective and widely used procedure to acquire lumbar lordosis for the surgical treatment of ASD [ 11 , 12 , 13 ]. Additionally, obtaining appropriate lumbar lordosis for any type of lumbar degenerative disease is essential when fusing any segment to achieve long-term goals.…”
Section: Introductionmentioning
confidence: 99%